Influence of Local Taxes, Local Levies and Local Taxes Moderated By Taxpay-er Compliance With Regional Original Income (Case Study on East Java Provincial Revenue Agency 2016 - 2020) - Ramadhan Aji Pamungkas; Gideon Setyo Budiwitjaksono; Tituk Diah Widayantie (Basic and Applied Accounting Research Journal, 2021)
This research is about the empirically testing and analyzing the local tax effect, regional levies and the taxpayer compliance moderating the effected from local tax at the regional original income at the East Java province in 2016-2020. The population in this study is all data on Tax Regional, Regional Levies and Original Revenues Regional each month during the 2016 - 2020 period as many as 60 regional tax reports, regional levies, regional original income and taxpayer compliance based on targets and their realization. The selection of this research sample carried out using census method. Techniques of analysis and hypothesis test from this study result with PLS. From the Path Coefficient, the following result are shown: Regional Tax has an effect on Regional Original Income, Regional levies and Regional Tax moderated by Taxpayer Compliance has no effect on Regional Original Income.